Role of MicroRNAs and Long Non-Coding RNAs in Regulating Angiogenesis in Human Breast Cancer: A Molecular Medicine Perspective - Golhani, Vandana; Ray, Suman K.; Mukherjee, Sukhes (Current Molecular Medicine, 2022)
MicroRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are proficient in regulating gene expression post-transcriptionally. Considering the recent trend in exploiting non-coding RNAs (ncRNAs) as cancer therapeutics, the potential use of miRNAs and lncRNAs as biomarkers and novel therapeutic agents against angiogenesis is an important scientific aspect. An estimated 70% of the genome is actively transcribed, only 2% of which codes for known protein-coding genes. Long noncoding RNAs (lncRNAs) are a large and diverse class of RNAs > 200 nucleotides in length, and not translated into protein, and are of utmost importance and it governs the expression of genes in a temporal, spatial, and cell context-dependent manner. Angiogenesis is an essential process for organ morphogenesis and growth during development, and it is relevant during the repair of wounded tissue in adults. It is coordinated by an equilibrium of pro-and anti-angiogenic factors; nevertheless, when affected, it promotes several diseases, including breast cancer. Signaling pathways involved here are tightly controlled systems that regulate the appropriate timing of gene expression required for the differentiation of cells down a particular lineage essential for proper tissue development. Lately, scientific reports are indicating that ncRNAs, such as miRNAs, and lncRNAs, play critical roles in angiogénesis-related to breast cancer. The specific roles of various miRNAs and lncRNAs in regulating angiogenesis in breast cancer, with particular focus on the downstream targets and signaling pathways regulated by these ncRNAs with molecular medicine perspective, are highlighted in this write-up.
Keywords: molecular medicine